Monoamino Oxidase A Gene Single-Nucleotide Polymorphisms and Methylation Status and the Risk of Violent Suicide Attempts in Affective Disorder Patients - Ludwig, Birgit; Carlberg, Laura; Kienesberger, Klemens; Swoboda, Patrick; Mitschek, Marleen M. M.; Bernegger, Alexandra; Koller, Romina; Inaner, Michelle; Senft, Birgit; Meisner, Lisa; Fischer-Hansal, Daniela; Affenzeller, Andreas; et al. (Frontiers in Psychiatry, 2021)
Background: When investigating the neurobiology of suicidal behavior, Monoamino Oxidase A (MAOA) is one of the prime suspects to consider. Interestingly, MAOA dysregulation has also been associated with violent behavior in previous publications. In the present study, we aimed to establish an association between polymorphisms of the MAOA gene and methylation status of the MAOA gene Exon I, and suicide attempts with violent methods in a sample of affective disorder patients. Methods: Eight hundred fourteen Caucasian affective disorder patients were assessed at the Department of Psychiatry and Psychotherapy of the Medical University Vienna, the Karl Landsteiner University for Health and Science and Zentren für seelische Gesundheit, BBRZ-Med Leopoldau. An assemblage of psychiatric interviews was performed (e.g. SCAN, HAMD, SBQ-R, CTQ) and DNA samples of peripheral blood cells were collected for Sequenom MassARRAY® iPLEX Gold genotyping and Multiplexed and Sensitive DNA Methylation Testing. Results: Female affective disorder patients with a history of violent suicide attempt were found to have a significantly increased frequency of the AA genotype in the rs5906957 single nucleotide polymorphism (p = 0.003). Furthermore, the MAOA gene exon I promoter region was significantly hypomethylated in female violent suicide attempter(s) as opposed to female affective disorder patients who had no history of suicide attempt or no history of suicide attempt with violent method. Limitations: The small sample size hampers to reveal small genetic effects as to be expected in psychiatric disorders. Conclusions: This study offers promising findings about associations between the MAOA gene and violent suicide especially in women.